Assessment of a National Diabetes Education Program diabetes management booklet: The GRADE experience. Issue 5 (18th February 2017) - Devchand, Roshni; Nicols, Christina; Gallivan, Joanne M.; Tiktin, Margaret; Krause‐Steinrauf, Heidi; Larkin, Mary; Tuncer, Diane M.; ,
Abstract: Background and purpose: The National Diabetes Education Program created the 4 Steps to Manage Your Diabetes for Life ( 4 Steps ) booklet to help patients with diabetes learn the basics of self‐management and care recommendations. The purpose of this study is to explore the impact of 4 Steps on participants' diabetes management knowledge and self‐efficacy in the Glycemia Reduction Approaches in Diabetes: A Comparative Effectiveness Study (GRADE). Methods: A sample of 348 adults with type 2 diabetes enrolled in GRADE was included in this analysis. Participants took a pretest, were sent home with 4 Steps, then took a posttest at their next visit. The Wilcoxon signed rank test was used to detect differences in knowledge and self‐efficacy between scale scores pre‐ and posttest. Conclusions: Analyses revealed increases in participants' diabetes management knowledge ( p < .001) and self‐efficacy ( p < .001) from pre‐ to posttest. Participants who reported no formal previous diabetes education showed a statistically significant increase in knowledge scores compared to those with previous diabetes education ( p < .05). Implications for practice: Appropriate, relevant diabetes education materials may improve self‐management knowledge and self‐efficacy among adults with type 2 diabetes. Providers should feel confident using 4 Steps as a resource for clinical practice.